Fuel Cells: Bulk Metallic Glass Micro Fuel Cell (Small 12/2013). Issue 12 (14th June 2013) - Sekol, Ryan C.; Kumar, Golden; Carmo, Marcelo; Gittleson, Forrest; Hardesty‐Dyck, Nathan; Mukherjee, Sundeep; Schroers, Jan; Taylor, André D.
<x xml:space="preserve">Abstract</x> The first all‐bulk metallic glass (BMG) micro fuel cell is designed by A. D. Taylor and co‐workers, consisting of Pt‐based BMG electrodes and Zr‐based BMG endplates. BMGs are amorphous metal alloys readily formed into a variety of shapes and sizes. The Pt–BMG electrode with high catalytic activity takes advantage of multi‐length scale thermoplastic forming to produce nanowires supported on a disc with 110 μm pores. Zr–BMG has superior corrosion resistance and conductivity beyond silicon, stainless steel, and graphite. On page 2081, this fuel cell is demonstrated for the first time as a flow field current collector. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>